Adherence to good practices in membrane premature rupture. Perinatology Service. University Hospital “Dr. Gustavo Aldereguía Lima”, Cienfuegos city. From January to December 2002. - Yusimi Miranda Pérez; Norma Mur Villar; Liudmila de Armas Rey; Yosleidy Capote Fragoso (Medisur)
Fundament:Nursing good practice demands standardizationof care,in such a way that they guide and unite the different ways of performance. Objetive: to determine the adherence of the care plan to the guide of good nursing practice in the premature rupture of the membranes and the level of the staff for the level of preparation for its performance in the Service of Perinatology. Methods: Descriptive, correlational and prospective study applied to 622 pregnant women admitted at the Perinatology Service of ¨Dr. Gustavo Aldereguía Lima¨ Hospital from Cienfuegos province who had a rupture of the membrane. 311 patients (50%) of the universe, selected with probabilistic simple randomized way, without exclusive criteria were studied. Adherence was measured by using evaluation means. Results:43 % of the assessed clinical records, received between 95 and 100 points . Among the 16 nurses evaluated , 43,7 % had difficulties, being 25 % technicians.